Talk Show Peran Perbankan Syariah di Era Pandemi - Suryani Suryani; Siti Marfu’ah; Elsa Elsa; Ratu Humaemah; Rezky Mehta Setiadi; Muhamad Fadli Azim; Jamaluddin Jamaluddin; Dian Febriyani (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Islamic banking has a strategic role in Indonesia’s economic development. Covid-19 pandemic has spread to various countries, including Indonesia. As a result, almost all sectors experienced contractions, including Islamic banking. However, Islamic banking is considered quite capable of surviving the storm of impact based on the previous crises' empirical facts. Several studies have proven and strengthened the theory that the profit and loss sharing used in Islamic bank is able to withstand pandemic conditions.